Disseminated zygomycosis due to Mycocladus corymbifera with cutaneous and cerebral involvement. (5th May 2011) - Schofield, Clare; Stern, Alexander; Jevtic, Andrew
ABSTRACT Fungal infections caused by zygomycetes are important and potentially life threatening infections. These opportunistic moulds have been increasingly implicated in human disease and are most frequently seen in immune compromised patients. We report a case of disseminated infection with Mycocladus corymbifera involving the brain, lungs, kidneys and skin in a 16‐year‐old patient with acute lymphoblastic leukaemia. The skin lesions played a significant role in the diagnosis of mucormycosis. These infections have an exceedingly high mortality rate and early recognition of cutaneous lesions is essential to successful management.